Volatile phenolics: A comprehensive review of the anti-infective properties of an important class of essential oil constituents. (October 2021) - Ahmad, Aijaz; Elisha, Ishaku Leo; van Vuuren, Sandy; Viljoen, Alvaro
Abstract: Historically, essential oils and their lead molecules have been extensively recognised for their anti-infective properties. In this context, certain volatile phenolics (VPs) have emerged as important antimicrobial compounds with excellent inhibitory activity against pathogenic bacteria and fungi, which further extends to drug-resistant and biofilm-forming micro-organisms. In this review, we aim to collate and discuss a number of published papers on the anti-infective activities of naturally occurring VPs with special emphasis on eugenol, isoeugenol, thymol and carvacrol, using Scopus Web of Science and PubMed databases. The biosynthesis and extraction of these VPs are discussed, while particular attention is given to their broad-spectrum antimicrobial activity and the mechanisms of action. We highlight combinational studies of the VPs with other phytocompounds and with commercially available drugs, which may be a promising and a rewarding future approach to combat antimicrobial resistance. These VPs alone, or concomitantly with other compounds or drugs, have the potential to be incorporated into different formulations for biomedical applications. An in-depth assessment of 2310 articles retrieved from the Scopus database spanning a 35-year period indicated 23.1% increase in global publication growth in VPs anti-infective research, with authors from Italy, Portugal and Austria dominating the research landscape. The dominant areas of investigations are identified as antimicrobial activity, antibacterial mechanism of action, antifungal mechanism of action, extraction methods and phytochemistry, use in the food industry, and for oral and dental anti-infective activity. Specific research areas, which require future attention include; antituberculosis research, nanoparticle formulation of antimicrobial active VP molecules, preclinical and clinical trials. The antimicrobial testing of isoeugenol was found to be the least studied of the VPs and this requires further attention. Graphical abstract: Image 1 Highlights: A bibliometric analysis of four volatile phenolics over 35-year period is presented. Thymol, carvacrol, eugenol and isoeugenol reviewed, isoeugenol requires future attention. Antimicrobial mechanistic actions and combination studies are explored.